Clinical evaluation of full‐arch screw‐retained implant‐supported fixed prostheses and full‐arch telescopic‐retained implant‐supported fixed prostheses: A 5–12 year follow‐up retrospective study. Issue 3 (5th February 2019) - Mori, Gentaro; Oda, Yukari; Sakamoto, Kei; Ito, Taichi; Yajima, Yasutomo
Abstract: Objective: To assess the prostheses and implants survival rate and peri‐implantitis rate in edentulous patients treated with full‐arch screw‐retained implant‐supported fixed dental prostheses (FSIFDPs) and full‐arch telescopic‐retained implant‐supported fixed dental prostheses (FTIFDPs) over an observation period of at least 5 years. Materials and methods: From 2004 to 2012, 696 implants were inserted into 78 patients with 102 prostheses. The FSIFDP group comprised 31 patients (37 prostheses, 232 implants), whereas the FTIFDP group comprised 47 patients (65 prostheses, 464 implants). Prosthesis and implant estimated cumulative survival rates (ECSR) and estimated cumulative peri‐implantitis rates (ECPR) were assessed. The follow‐up period was 5–12 years. Kaplan–Meier survival curves with the log‐rank test were used to evaluate outcomes. Results: The 12‐year prosthesis ECSR was 96.8% (95% CI: 79.2–99.5, 36/37 prostheses) in the FSIFDP group and 96.4% (95% CI: 86.3–99.1, 63/65 prostheses) in the FTIFDP group, whereas the 12‐year implant ECSR was 99.5% (95% CI: 96.4–99.9, 231/232 implants) in the FSIFDP group and 98.7% (95% CI: 96.9–99.5, 459/464 implants) in the FTIFDP group. The 12‐year ECPR at the prosthesis level was 12.8% (95% CI: 12.7–47.6, 4/37 prostheses) in the FSIFDP group and 12.8% (95% CI: 11.4–24.1, 6/65 prostheses) in the FTIFDP group. The 12‐year ECPR at the implant level was 4.4% (95% CI: 4.3–23.0, 6/232 implants) in the FSIFDP group and 2.2% (95% CI: 2.0–12.3, 7/464 implants) in the FTIFDP group. Conclusion: FTIFDPs have clinical results comparable to those of FSIFDPs. Therefore, FTIFDPs can be useful.